Measurement of the cross section for electromagnetic cissociation with neutron emission in Pb-pb collisions at √sNN=2.76 TeV - Abelev, Betty; Busch, Oliver; Engel, Heiko; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Krawutschke, Tobias; Kweon, MinJung; Lara Martinez, Camilo Ernesto; Lohner, Daniel; Mercado Pérez, Jorge; Oyama, Ken; et al. (Physical review letters, 2012)
The first measurement of neutron emission in electromagnetic dissociation of 208Pb nuclei at the LHC is presented. The measurement is performed using the neutron zero degree calorimeters of the ALICE experiment, which detect neutral particles close to beam rapidity. The measured cross sections of single and mutual electromagnetic dissociation of Pb nuclei at √sNN=2.76 TeV with neutron emission are σsingleEMD=187.4±0.2(stat)+13.2−11.2(syst) b and σmutualEMD=5.7±0.1(stat)±0.4(syst) b, respectively. The experimental results are compared to the predictions from a relativistic electromagnetic dissociation model.